Alcohol consumption in pregnancy is under-recognised. (7th June 2011) - Aiton, N R; Mattis, J
Abstract : Hypothesis: Women who drink alcohol in pregnancy are under-recognised. Background: National and local data suggest that 22–26% of women of child-bearing age drink greater than 14 units of alcohol per week. Spontaneous abortion rates are 5-fold higher in those who drink more than 5 units per week. One study has shown that 10% of women in the USA may continue to drink alcohol in pregnancy, but the prevalence in the UK is unknown. National Institute for Health and Clinical Excellence recommends that women are screened for alcohol use in pregnancy as part of routine antenatal care. Method: Audit of referrals to a specialist substance misuse clinic for pregnant women in Brighton in 2009, a city with a delivery rate of approximately 3700 per year. Results: There were 62 women referred (1.7% of all deliveries) who were recorded as having alcohol misuse. From these 62, only 12 women did not misuse any other substances in addition to alcohol. 27 of these women (0.7% of all deliveries) were referred by community midwives: only 5 of whom used alcohol alone. In the remainder referral was almost always for misuse of other substances. Conclusion: Referral by midwives for alcohol use alone was very unusual. Alcohol use in pregnancy is probably under-recognised. Further work is required to determine the true prevalence of alcohol use in pregnancy in the UK, and increase our ability to recognise these women so that they can receive the appropriate interventions to decrease drinking and improve health outcomes for mother and baby.